How residents behave: home range flexibility and dominance over migrants in a Mediterranean passerine. (January 2017) - Morganti, Michelangelo; Assandri, Giacomo; Aguirre, José Ignacio; Ramirez, Álvaro; Caffi, Mario; Pulido, Francisco
Abstract : Residency has repeatedly evolved in many migratory animals, some of which have preserved the anatomical adaptations to perform long-range movements. This is the case for partially migratory populations of Mediterranean passerines in which migrants and residents both have a migrant morphology. The question of how selection maintains residency in this situation remains unclear. Using radiotelemetry, we followed the resident fraction of a partially migratory population of blackcaps, Sylvia atricapilla, from eastern Spain and studied changes in home range size and habitat composition throughout three breeding and two wintering seasons. We then compared these birds with two groups of migratory blackcaps present in the area: in winter with migrants that breed in northern populations and in spring with migrants that breed locally. In addition, we observed aggressive interactions between individually marked birds to explore dominance relationships during winter. The home ranges of resident blackcaps were six times larger in winter than during the breeding season, but within each season, they were comparable in size to those of migrants. The habitats used by residents markedly differed between seasons as well as from those of migrants in winter, but not during the breeding season. In winter, resident birds were dominant over migrants, although migrants were generally larger. Overall, residents showed high between-season flexibility in home range size and habitat use. Winter home ranges of residents included breeding sites and more diverse types of habitats than those of northern migrants. This suggests that in winter, the importance of dominance for obtaining priority access to food may be high but not crucial, given that residents may reduce competition by feeding separately from migrants. Future studies should focus on whether residents show specific personalities and on the role of yearly oscillations in environmental conditions in maintaining residency in this type of partially migratory population. Highlights: We studied behaviour of wild resident blackcaps during breeding and wintering. Breeding home ranges of migrants and residents were similar in size and composition. In winter, residents use more habitat types than migrants. Winter home ranges of residents include breeding ones, which are six times smaller. Residents, although smaller, are dominant over migrants wintering in the same area.